Safety profile of complement C5 inhibitors and FcRn inhibitors in the treatment of myasthenia gravis: analysis of the FAERS database and disease-gene interaction network - Wang, Luqiong; Chen, Jiaojiao; Li, Huixiang; Wang, Lin; Liu, Feiyu; Jiang, Xiaoli (Frontiers in Immunology, 2025)
ObjectiveTo integrate pharmacovigilance and network pharmacology methods for a comprehensive analysis of the potential adverse reactions of complement C5 inhibitors (eculizumab, ravulizumab, zilucoplan) and neonatal Fc receptor (FcRn) inhibitors (efgartigimod, rozanolixizumab), and to explore their toxicity mechanisms, thereby providing a reference for rapidly understanding the safety of these two novel classes of biologics in the treatment of myasthenia gravis (MG).MethodsWe extracted adverse event (AE) reports for these five drugs from the FDA Adverse Event Reporting System (FAERS) database, limited to the period since their FDA approval for the treatment of MG. Reports were further restricted to those where the drug was listed as the primary suspect (PS) and the indication (INDI) was “MG”. Signal detection was performed using the Reporting Odds Ratio (ROR) method, the UK Medicines and Healthcare products Regulatory Agency (MHRA) method, and the Bayesian Confidence Propagation Neural Network (BCPNN) method. Additionally, network pharmacology was employed to analyze the toxicity mechanisms of the system organ categories (SOCs) specifically associated with complement C5 inhibitors and FcRn inhibitors.ResultsSignal detection of AE reports associated with these five drugs revealed previously unlabeled positive signals, including: eculizumab (gastric cancer, embolic stroke), ravulizumab (psoriatic arthropathy, hypoacusis, peripheral vascular disorders), zilucoplan (weight increased, weight decreased), efgartigimod (metastases to liver, hepatic failure, nephrolithiasis, dysuria, Prostatitis, prostate cancer, Angina pectoris, congestive cardiac failure) and rozanolixizumab (vomiting, dyspepsia). However, the gastric cancer, liver metastasis and prostate cancer were reported within the first 30 days, causal associations cannot be established based on the data presented. Potential toxicity analysis was conducted on noteworthy SOCs for complement C5 inhibitors and FcRn inhibitors, revealing key targets and pathways.ConclusionThis study elucidated the safety profiles of complement C5 inhibitors and FcRn inhibitors in clinical practice through pharmacovigilance analysis, confirming known adverse reactions and identifying several previously unreported ones. Furthermore, network pharmacology analysis revealed potential mechanisms underlying these adverse reactions. These findings provide valuable insights for monitoring and managing risks during treatment with two novel classes of biologics.